Supply chain network redesign to make resiliency with proposing “two-phase establishment facilities” as risk mitigation strategy - Mohammad Yavari; Mohsen Aghelan (مجله مدل سازی در مهندسی, 2019)
Supply chain network resilience is a serious challenge in the supply chain management. The existing researches in the literature focused on creating resilience in design of new supply chain networks, and creating resilience in supply chain has not been addressed in previous studies. This research investigated supply chain network redesign to make supply chain resilience. For this purpose a mixed integer linear programing model is developed considering two existing risk mitigation strategies, consisting of “the extra capacity” and “the emergency stock”, and a new strategy called "two-phase facility". The proposed “two-phase strategy” is applied in two echelons of distribution centers and retailers. Eventually, numerical experiments have been conducted to evaluate and compare the performance of the resilient and non-resilient supply chain networks as well as to compare the efficiency of risk mitigation strategies. Results revealed that resilient supply chain enjoys 4.5% and 5.5% higher performance in compared with non-resilient supply chain in terms of supply capability and profit, respectively.